Assessment of Knowledge, Attitude and Preventive Practices towards Sexually Transmitted Infections among Secondary School Students in Mlimba Division, Ifakara, Tanzania - J. Kavana, Nicholas (International Journal of Sexually Transmitted Diseases, 2021)
Background This study was done to assess knowledge, attitude and preventive practices towards sexually transmitted infections among secondary school students in Mlimba Division, Ifakara, Tanzania. Method A descriptive cross-sectional study was conducted in March 2021. A total of 365 secondary school students (193 male; 172 female) aged between 12 and 23 years were surveyed by using a pretested self-administered questionnaire. Results The study found the majority 95.9% had heard of STDs, 77.8% knew symptoms of STDs, 86.8% knew mode of transmission, 94.0% knew the importance of use of condom during sexual intercourse. Among the sexually-active students, 70.7% had practiced sexual intercourse and 42.2% used condom during sexual intercourse. Conclusion The risky behavior practiced by the sexually-active students in this study is alarming. There is a need to introduce STD education curriculum in secondary schools so that appropriate intervention on STDs can be implemented.
Keywords: Sexually transmitted infections; secondary school students; Knowledge; Attitude; Practice